Combination Therapy with Oleanolic Acid and Metformin as a Synergistic Treatment for Diabetes - Xue Wang; Yupeng Chen; Daoud Abdelkader; Waseem Hassan; Hongbin Sun; Jun Liu (Journal of Diabetes Research)
Aims and Background. Type 2 diabetes is a chronic disease that cannot be treated adequately using the known monotherapies, especially when the disease progresses to an advanced stage. In this study, we explore the possibility of treating the disease with a novel combination approach of oleanolic acid (OA), a glycogen phosphorylase (GP) inhibitor, and metformin. Methods. Db/db mice were randomly divided into four groups: a db/db control group, db/db mice treated with OA (250 mg/kg), db/db mice treated with metformin (100 mg/kg), and db/db mice treated with a combination of OA and metformin. All mice were treated for four weeks. The effects of the treatments on glucose homeostasis were measured using an OGTT, an assessment of insulin sensitivity and signaling in the liver, and the hepatic glucose production. Results. Combination therapy with OA and metformin significantly reduced the blood glucose and insulin levels and improved the liver pathology compared with that for the monotherapy in the db/db diabetic mouse model. We also found that the combination therapy significantly increased the mRNA expression of glycogen synthesis and decreased the GP, PGC-1α, PEPCK1, and G-6-Pase levels. In addition, the combination therapy with OA and metformin significantly increased the phosphorylation of AKT, PI3K, AMPK, and ACC and decreased the protein expression levels of G-6-Pase, PEPCK1, and TORC compared with those for either monotherapy. The combination therapy also reduced the phosphorylation of mTOR and CREB. Conclusions. Our results suggest that the combination therapy with OA and metformin has synergistic effects on the symptoms of db/db diabetic mice by improving glucose and insulin homeostasis.